Investigation Perspectives of Dynamics of Tank Vehicles for Liquid Loads - A.O. Shimanovsky (Механика машин, механизмов и материалов, 2007)
It is analysed a current state and investigation perspectives of dynamics truck and rail tank vehicles. There are resulted equations presenting movement of considered system members. The equations of continuum mechanics for the description of liquid movement, and the dynamic equations of mechanics of rigid body for vehicle structure are used. There are evaluated problem solvings about rolling stability of tank cars, about optimization of tank shape, and also about effect of damping baffle on the kinematic and dynamic parameters of tank vehicle movement by means of the examined equations.